In regard to Levi-Strauss’s "motive of oblivion". Structure of disturbed communication and styles of thoughts in transitory Serbia - Dragana Antonijević (University of Belgrade, 2016)
This paper starts with Levi-Strauss’s semantic concept that consists of oblivion, misunderstanding, indiscretion and nostalgia. Through his analysis of North American and Greek myths, Levi-Strauss concluded that "semantic filed of oblivion" has an important meaning especially in the construction of particular rules and rituals; or, in other words, it has an important part in the introduction of culture to the nature of cognitive and social processes.